High-resolution, non-crystallographic structural studies of large integral membrane proteins. - Watts, A (1994)
The work described here clearly demonstrates that n.m.r. is a viable method with which to resolve molecular details about membrane proteins and can give information at a resolution comparable with that gained from crystallographic studies, where, in the limited number of cases studied so far, such information is available. Sensitivity is not a major problem although other difficulties may prevent particular kinds of information being resolved. However, because bond orientational details are obtained ab initio, the method is quite model independent and interpretationally unique. The requirements for solid-state n.m.r. methods to be applied to a large membrane protein are that: a sufficient amount of functionally active protein is available; the protein should be located in bilayers; and suitable specific isotopic enrichment is achieved, in ideal cases, either by chemical or biosynthetic means. Achieving these requirements will need to draw on a range of skills, possibly genetic or chemical or both, and a full understanding of the biochemistry is essential to ensure that any structural information gained is functionally relevant. The structural information potentially available includes: (a) conformation details about specific parts of a protein or its binding sites; (b) distance measurements between specific labels introduced into the protein; (c) dynamics of particular parts of the protein; (d) chain folding and residue orientation; and (e) the mechanistic changes that can occur during a functional cycle. Much developmental work still needs to be done both on the sample handling instrumental side and with the theoretical aspect of the method.(ABSTRACT TRUNCATED AT 250 WORDS)